(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Phenomenon of Metaphorization in the Romanian Religious LanguageThis artticle broaches the study of religious metaphorical language which, at the key of the Aristotelian idea, represents the connection between the irrational and the rational. One of the metaphorical terms is considered a basic code, usually being a word belonging to the lexical field of sacrality, another term means a sign from reality. The metaphorical equation is constituted on the principle of circular metaphorization, through which one metaphor starts from another.